36 Triple Therapy Anticoagulation following Percutaneous Coronary Intervention (PCI) with Novel Oral Anticoagulants (NOAC) is Safe and has no Adverse Effects on Bleeding Post Procedure when Compared to Triple Therapy with Vitamin K Antagonist (VKA). (3rd June 2016) - Amin, Reshma; McWilliams, Nicholas; Lee, Deacon; Altaf, Fatima; Virani, Farzana; Dickinson, Katherine; Walker, David; Sharp, Andrew; Gerber, Robert
Abstract : Introduction: Following PCI, dual antiplatelet therapy (DAPT) is indicated for prevention of stent thrombosis. An increasing number of patients also require long term oral anticoagulation for stroke prevention in atrial fibrillation, for mechanical heart valves and venous thromboembolism. Bleeding rates are historically higher in patients on triple therapy anticoagulation when compared to those on DAPT. Since the introduction of NOAC, there are a variety of combinations of triple therapy anticoagulation that patients can be commenced on following PCI; however the bleeding risks between these groups are yet to be compared. Methods: We retrospectively studied 853 patients who underwent PCI in one centre from 2013–2014. Of these, 103 patients required triple therapy, 49 with a Vitamin K antagonist (VKA) and 54 with NOAC. The primary endpoint was 12 month bleeding complications as categorised by the Bleeding Academic Research Consortium (BARC). The secondary endpoint was major adverse cardiovascular and cardiac events (MACCE). Results: Of those on Triple Therapy Anticoagulation, 69% of patients were male and 32% were aged 75 or above. The indications for anticoagulation were AF (74%), Venous Thromboembolism (12%), left ventricular thrombus (13%) and mechanical heart valve (1%) Of those anticoagulated for AF, 95% had a CHA2ds2-VASc score greater than 2. 29% of PCI was performed for NSTEACS and 17% for ST segment elevation MI. In the VKA category there was 12% minor bleeding compared to 22% in NOAC group (p0.0419). There was no significant difference between TIMI Major and BARC bleeding between the two groups. MACCE in the VKA group was 12% and in the NOAC group 5% of which. (p = 0.0412) Conclusion: There is no significant difference in the bleeding risk between patients taking triple therapy anticoagulation following PCI with a NOAC or a VKA. Patients requiring triple therapy anticoagulation following PCI have significantly less risk of MACCE at 12 month follow up with NOAC compared to VKA.